Balance of payments dilemmas - W. J. Feuerlein (Intereconomics, 1972)
An analysis of the recurring International monetary crises raises the question whether the monetary adjustments alone will be an adequate weapon to deal with them or whether additional none-monetary steps should also be taken.
Keywords: 330; Monetary Policy